Comprehensive RNA-Seq Data Analysis Identifies Key mRNAs and lncRNAs in Atrial Fibrillation - Wu, Dong-Mei; Zhou, Zheng-Kun; Fan, Shao-Hua; Zheng, Zi-Hui; Wen, Xin; Han, Xin-Rui; Wang, Shan; Wang, Yong-Jian; Zhang, Zi-Feng; Shan, Qun; Li, Meng-Qiu; Hu, Bin; et al. (Frontiers in Genetics, 2019)
Long non-coding RNAs (LncRNAs) are an emerging class of RNA species that may play a critical regulatory role in gene expression. However, the association between lncRNAs and atrial fibrillation (AF) is still not fully understood. In this study, we used RNA sequencing data to identify and quantify the both protein coding genes (PCGs) and lncRNAs. The high enrichment of these up-regulated genes in biological functions concerning response to virus and inflammatory response suggested that chronic viral infection may lead to activated inflammatory pathways, thereby alter the electrophysiology, structure, and autonomic remodeling of the atria. In contrast, the downregulated GO terms were related to the response to saccharides. To identify key lncRNAs involved in AF, we predicted lncRNAs regulating expression of the adjacent PCGs, and characterized biological function of the dysregulated lncRNAs. We found that two lncRNAs, ETF1P2 and AP001053.11, could interact with protein-coding genes (PCGs), which were implicated in AF. In conclusion, we identified key PCGs and lncRNAs, which may be implicated in AF, which not only improves our understanding of the roles of lncRNAs in AF, but also provides potentially functional lncRNAs for AF researchers.